Efektivitas Pengembangan E-Book Fisika Berbasis Discovery Learning Tema Gempa Bumi untuk Meningkatkan Kompetensi Sikap Tangguh Peserta Didik - Fitrah Ayu; Ahmad Fauzi (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2021)
The problem in this research is that the attainment of competence attitudes of students is still not optimal, namely the tough attitude of students in facing earthquake disasters. This development research aims to determine the level of effectiveness of using the integrated Physics e-book material for earthquake disaster mitigation in physics learning to improve the competence of students' resilient attitude. This type of research is Research and Development (R&D). The development model used is the Plomp development model which consists of three stages, namely the preliminary research phase, the development or prototyping phase, and the assessment phase. This study only describes the results of the assessment phase, namely the competence of students' attitudes. The method used in this research is descriptive method with data collection instruments, namely self-assessment in the form of questionnaires filled out by students. This research was conducted at 14 Padang Senior High School for the 2019/2020 Academic Year on wave material. The results of this study indicate that the integrated physics e-book earthquake mitigation material is effectively used in the learning process with the average percentage of students' attitudes for three meetings, namely 81% in the very effective category.